RGD Peptide-Grafted Graphene Oxide as a New Biomimetic Nanointerface for Impedance-Monitoring Cell Behaviors - Jianxia Li (Journal of Nanomaterials, 2016)
A new biomimetic nanointerface was constructed by facile grafting the bioactive arginylglycylaspartic acid (RGD) peptide on the graphene oxide (GO) surface through carbodiimide and N-hydroxysuccinimide coupling amidation reaction. The formed RGD-GO nanocomposites own unique two-dimensional structure and desirable electrochemical performance. The linked RGD peptides could improve GO’s biocompatibility and support the adhesion and proliferation of human periodontal ligament fibroblasts (HPLFs) on RGD-GO biofilm surface. Furthermore the biologically active RGD-GO nanocomposites were demonstrated as a potential biomimetic nanointerface for monitoring cell biobehaviors by electrochemical impedance spectroscopy (EIS). By analysis of the data obtained from equivalent circuit-fitting impedance spectroscopy, the information related to cell membrane capacitance, cell-cell gap resistance, and cell-electrode interface gap resistance in the process of cell adhesion and proliferation could be obtained. Besides, this proposed impedance-based cell sensor could be used to assess the inhibition effect of the lipopolysaccharide (LPS) on the HPLFs proliferation. Findings from this work suggested that RGD peptide functionalized GO nanomaterials may be not only applied in dental tissue engineering but also used as a sensor interface for electrochemical detection and analysis of cell behaviors in vitro.